The Clinical Link between Type D Personality and Diabetes - Conti, Chiara; Carrozzino, Danilo; Patierno, Chiara; Vitacolonna, Ester; Fulcheri, Mario (Frontiers in Psychiatry, 2016)
Introduction: Type D personality consists of a mixture of high levels of Negative Affectivity and Social Inhibition, resulting in a stable tendency to experience negative emotions, by inhibiting the expression of these emotions. We have reanalyzed the clinically relevant studies examining the role of this personality profile in diabetes, by providing a qualitative synthesis of the data. In this regard, the aim of this study is to provide a systematic review by evaluating the clinical link between Type D personality and diabetes. Method: When focusing on PRISMA guidelines, we have performed a comprehensive research of the literature on PubMed, Scopus, ScienceDirect, ISI Web of Science, PsycINFO, and Google Scholar by using as search terms ‘distressed personality’ OR (i.e., Boolean operator) ‘Type D personality’ combined with the Boolean ‘AND’ operator with ‘diabetes’. Results: A total of 7 research studies were identified and included in the review. Type D was found to be more prevalent in diabetes patients than controls. As regards the specific association with diabetes variables, Type D personality is a significant predictor of both poor medication adherence and unhealthy behaviors, by predicting also negative mental health consequences (i.e., depressed mood, anhedonia and anxiety). Conclusion: Our review emphasized for the first time that Type D personality affects clinical factors in patients with diabetes by provoking adverse outcomes. The core implication of the study comprises the clinical relevance to detect, from a clinimetric point of view, Type D personality in diabetes in order to prevent potentially negative clinical outcomes.